2020
DOI: 10.3390/ijerph17134909
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Controlling Interpersonal Coaching Style, Basic Psychological Need Thwarting, and Burnout, in Adolescent Soccer Players

Abstract: The aim of this paper is to analyze the relationships between a controlling interpersonal style, psychological need thwarting and burnout in adolescent soccer players and to test a structural equation model to analyze whether (a) a controlling interpersonal style is a predictor of psychological need thwarting and whether (b) psychological need thwarting is a predictor of burnout. A total of 103 male soccer players between the ages of 12 and 17 participated in the research (M = 14.91; SD = 5.56). The Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
2
4
1
4
Order By: Relevance
“…No significant differences were found in the rest of the variables. These results differ from those obtained in the study by Morales-Sánchez et al (2020), where the most important indicator within the control style variable was negative conditional regard, which could be defined as the denial of love, attention and affection when the athletes do not show the desired behaviours. Although it is true that, in the previous study, no differences were established in terms of gender, since the sample compendium was comprised exclusively of 103 male football players aged between 12 and 17 years old.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No significant differences were found in the rest of the variables. These results differ from those obtained in the study by Morales-Sánchez et al (2020), where the most important indicator within the control style variable was negative conditional regard, which could be defined as the denial of love, attention and affection when the athletes do not show the desired behaviours. Although it is true that, in the previous study, no differences were established in terms of gender, since the sample compendium was comprised exclusively of 103 male football players aged between 12 and 17 years old.…”
Section: Discussioncontrasting
confidence: 99%
“…The results confirmed a positive and significant relationship between all the study variables, highlighting those established between the athletes' perception of the coaches' or judo masters' interpersonal styles, and the frustration of their basic psychological needs, in agreement with studies such as those of , Mars et al (2017) or Morales-Sánchez et al (2020). In this latter study, they analysed the existing relationships between a controlling interpersonal style, frustration of psychological needs, and burnout in adolescent football players.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A more recent study by Atienza et al [ 4 ] with vocational dancers showed that autonomous motivation was negatively associated with burnout, and amotivation was positively associated with it, whereas controlled motivation was not linked to burnout. Other studies (e.g., [ 33 , 34 ]) have reported that perception of a controlling interpersonal coaching style had significant predictive power on thwarting each of the basic psychological needs (i.e., autonomy, competence, and relatedness), and these thwarted needs were positively associated with burnout.…”
Section: Introductionmentioning
confidence: 95%